A mirrow of others’ wills - López Ruiz, Patricia Teresa (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The purpose with which this work is conceived is with the intention of contrasting a spanish and a european novel, contemporary with each other, and whose central theme was adultery. Both presented to their protagonists with a very similar character, as well as to boring and asphyxiating cities that surrounded their existence. Through different structures, characters, descriptions, symbols and narrative resources will go to two endings, in which, although Effi dies and la Regenta does not, underlying the same idea: the influence of the environment on the character and health of its inhabitants, the discouragement and the fall of two beings because of the oppression exerted by the envies and wills of others.